Application of a multifunctional chemotherapy infusion device for reducing antineoplastic drug extravasation - Yang, Li-Hua; Liu, Li-Ping; Jiang, Fa-Ying; Huang, Feng-Zhu; Xie, Chun-Fen; Lin, Xue-Qin; Wang, Pan; Feng, Xiu-Li (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to address the challenges associated with antineoplastic drug extravasation during intravenous administration, through the development of a novel chemotherapy infusion device. A secondary objective was to mitigate associated risks to healthcare personnel, patients, caregivers and the environment.MethodsA water-soluble fluorescent solution was used as a surrogate for antineoplastic chemotherapy agents to assess the potential for drug extravasation and the associated risks of occupational exposure during intravenous administration. The investigation identified risks related to drug extravasation, which informed the development of the novel infusion device.ResultsIn experiment 1, conventional methods for replacing infusion bags resulted in drug extravasation during the second bag change across all procedures conducted by 9 operators. Specifically, extravasation was observed in 81 out of 90 procedures. In experiment 2, the newly designed multifunctional chemotherapy infusion device, which requires each infusion bag to be punctured only once, was used. Under these conditions, the same 9 operators performed 90 procedures, with extravasation occurring in only 2 instances.ConclusionThe multifunctional chemotherapy infusion device facilitates the efficient administration of intravenous chemotherapy while addressing the issue of drug extravasation associated with traditional infusion devices during the delivery of antineoplastic drugs. This device effectively reduces the risk of occupational injuries among healthcare workers, reduces harm to patients and their caregivers, and mitigates environmental contamination.